2006
DOI: 10.5326/0420312
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Severe Adverse Cutaneous Drug Reactions With Human Intravenous Immunoglobulin in Two Dogs

Abstract: Severe adverse cutaneous reactions were documented in two dogs with acute skin lesions and systemic signs after exposure to several oral and injectable drugs. Because of the high morbidity and mortality rates of many severe cutaneous drug reactions and a poor response to supportive care, wound management, and conventional immunosuppressive therapy, human intravenous immunoglobulin (IVIG) was infused on 2 consecutive days (1 g/kg per day) after informed consent was received. Human IVIG, with supportive care, re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 22 publications
0
35
0
Order By: Relevance
“…This is important because the exact depth of skin necrosis, when shallow, can be difficult to determine clinically, and histologic examination aids disease classification. There are examples in the literature of cases reported to be TEN 1,13,26 that lacked sufficient clinical criteria for TEN and had evidence of dermal necrosis; these were more likely examples of thermal injury or vascular disease in which dermal necrosis can be a feature.…”
Section: Discussionmentioning
confidence: 99%
“…This is important because the exact depth of skin necrosis, when shallow, can be difficult to determine clinically, and histologic examination aids disease classification. There are examples in the literature of cases reported to be TEN 1,13,26 that lacked sufficient clinical criteria for TEN and had evidence of dermal necrosis; these were more likely examples of thermal injury or vascular disease in which dermal necrosis can be a feature.…”
Section: Discussionmentioning
confidence: 99%
“…Toxic epidermal necrolysis is distinguished from a burn by the lack of dermal necrosis. Some cases described in the literature as TEN may be questionable, because significant dermal necrosis was reported . Distinguishing TEN histologically from acute graft‐versus‐host disease can be a major problem in transplantation patients …”
Section: Histological Lesionsmentioning
confidence: 99%
“…Human IVIG is extremely expensive and is rarely employed in animal cases. It has been used successfully in treating a cat with postvaccinal ‘EM’ and two dogs with probable drug reactions . A 2011 review of indications for hIVIG therapy suggested great promise for treatment of animal skin disease .…”
Section: Treatmentmentioning
confidence: 99%
“…Meanwhile, IVIg is effective for refractory systemic and cutaneous vasculitis in humans [1,10]. Recently, hIVIg was reported as effective and safe in the treatment of dogs with adverse cutaneous drug reactions and pemphigus foliaceus, which are severe immune-mediated skin diseases [12,19]. In this case, clinical improvement was not maintained by only IVIg, necessitating the use of other immunosuppressive drugs.…”
mentioning
confidence: 81%